A simulation study of disaggregation regression for spatial disease mapping. (17th October 2021) - Arambepola, Rohan; Lucas, Tim C. D.; Nandi, Anita K.; Gething, Peter W.; Cameron, Ewan
Abstract: Disaggregation regression has become an important tool in spatial disease mapping for making fine‐scale predictions of disease risk from aggregated response data. By including high resolution covariate information and modeling the data generating process on a fine scale, it is hoped that these models can accurately learn the relationships between covariates and response at a fine spatial scale. However, validating these high resolution predictions can be a challenge, as often there is no data observed at this spatial scale. In this study, disaggregation regression was performed on simulated data in various settings and the resulting fine‐scale predictions are compared to the simulated ground truth. Performance was investigated with varying numbers of data points, sizes of aggregated areas and levels of model misspecification. The effectiveness of cross validation on the aggregate level as a measure of fine‐scale predictive performance was also investigated. Predictive performance improved as the number of observations increased and as the size of the aggregated areas decreased. When the model was well‐specified, fine‐scale predictions were accurate even with small numbers of observations and large aggregated areas. Under model misspecification predictive performance was significantly worse for large aggregated areas but remained high when response data was aggregated over smaller regions. Cross‐validation correlation on the aggregate level was a moderately good predictor of fine‐scale predictive performance. While these simulations are unlikely to capture the nuances of real‐life response data, this study gives insight into the effectiveness of disaggregation regression in different contexts.